(untitled) - Kershenbaum, Aaron (New York, 1993)
This book is one of the few devoted to the design of telecommunications networks, and the first to deal with the topic in sufficient depth to allow the reader to actually solve network design problems on a realistic scale.
Keywords: Phân tích hệ thống,System analysis